en las relaciones sexuales contra Adolescentes mujeres por parte de otro Adolescente, no se puede admitir que exista Consentimiento, por lo que se debe tipificar y Penalizar como delito de violación - Eudaldo Benjamín, Cedeño Angulo (2015)
Relations between young people have become normal, however, we must remember that the first relationships, teenagers will form their first ideas about how it will be a relationship and how to behave in private, but It is not always true because for them, this is a new situation that will have to experiment and learn to relate, therefore, it is essential to live their sexuality in a healthy way at this stage and learn to respect others and respect themselves, regardless of whether the sexual act must take precedence at this stage of life, they should be aware that moral values are the first and most man or woman is not whether the act not experienced in adolescence sexual. This type of relationship is the phenomenon of sexual violence that began as a courtship process in youth groups, which is frowned upon by society, and that has become uncontrollable because young people always argue that the act was carried out with approval and therefore does not constitute a violation, this ignorance that teenagers are legal to consent or perform sex incapable, has resulted in Ecuadorian society there are thousands of mothers between fourteen and fifteen. These acts of sexual violence affects women and girls more vulnerable because of the social coercion dominant to submissive, it could also be applied to young people of the same sex, which we understand that there could be a significant difference between couples eterosexuales or homosexual It is common to hear those related to sexual violence in schools and peer teenage couples on the internet, personal blogs, paper, audiovisual media, etc. news, is remarkably abundant and, worst of all, most youngsters who are aged between 9 and 16 years, sexual violence by dominating or submission peer/as and between pairs of adolescents is directly related aggression among peers and between partners and always violence sex is more common in casual couples and mixed groups in pairs with more serious relationships, in both sexes, which differs sexual violence among adults; I am also sure that it is more frequent sexual violence in adolescents older than in younger, also tend to be less empathetic, more aggressive with teachers, boys and girls younger who most often lead to violence Sexual there as youth violence in intimate relationships and peer through the transfer of the domainsubmission scheme is that teenagers tend to identify with a social model based on the dominance of one and submission of the others; this is a hypothesis that I think is fundamental and tremendous attention because sexual violence is passed from one context to another, which leads me to think that being the aggressor/a with peers/as couples or in adolescence may be a risk factor to also be in adulthood; You can also perpetuate and establish the most likely